To do it without a calculator:
10% of 67 is 6.7
6.7 x 8 is 53.6 (80%)
1% of 67 is .67
<span>53.6 - .67 is 52.93 (79%)</span>
Answer:
y=2x-1
Step-by-step explanation:
y= 6x-1-4x
y=2x-1
Answer:
<h2>b = 4</h2>
Step-by-step explanation:
![0=-\dfrac{1}{4\!\!\!\!\diagup_1}\cdot16\!\!\!\!\!\diagup^4+b\\\\0=-4+b\qquad\text{add 4 to both sides}\\\\4=-4+4+b\\\\4=b\to b=4](https://tex.z-dn.net/?f=0%3D-%5Cdfrac%7B1%7D%7B4%5C%21%5C%21%5C%21%5C%21%5Cdiagup_1%7D%5Ccdot16%5C%21%5C%21%5C%21%5C%21%5C%21%5Cdiagup%5E4%2Bb%5C%5C%5C%5C0%3D-4%2Bb%5Cqquad%5Ctext%7Badd%204%20to%20both%20sides%7D%5C%5C%5C%5C4%3D-4%2B4%2Bb%5C%5C%5C%5C4%3Db%5Cto%20b%3D4)
350 cm^2 (A for connections academy)
Answer:For this case we have that by definition it is fulfilled:
Where:
a: It is the base
b: It is the exponent
So, if we have the following expression:
-6 to the power of 4, is equivalent to:
So we have to:
-6: It is the base
4: It is the exponent
-6: It is the base
4: It is the exponent
Step-by-step explanation: